2018
DOI: 10.17060/ijodaep.2018.n1.v4.1284
|View full text |Cite
|
Sign up to set email alerts
|

Parents knowledge about the development of children aged 2 to 6 years old.

Abstract: Based on the assumption that parental knowledge about child development influences the way parents understand the behavior of their children, parenting actions and child development, this study aimed to: 1) analyze what parents know about the development of children aged between 2 and 6 years old and the security they have on this knowledge; 2) explore the variability of this knowledge according to characteristics such as age, sex, parents’ level of education and number of children; 3) know if parental knowled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 14 publications
0
7
0
2
Order By: Relevance
“…The present study demonstrated that adults' perceptions of children are affected by the child's age (4 or 10 years old), the domain of memory error (academic or social), and to some extent the type of memory error (PM or RM), and that these ratings differ depending on the amount of prior experience an individual has with children (similar to Furnham et al, 2003;Vale-Dias & Nobre-Lima, 2018). Children, regardless of age, who make social memory errors are perceived more negatively than when they make academic errors.…”
Section: Discussionmentioning
confidence: 65%
See 4 more Smart Citations
“…The present study demonstrated that adults' perceptions of children are affected by the child's age (4 or 10 years old), the domain of memory error (academic or social), and to some extent the type of memory error (PM or RM), and that these ratings differ depending on the amount of prior experience an individual has with children (similar to Furnham et al, 2003;Vale-Dias & Nobre-Lima, 2018). Children, regardless of age, who make social memory errors are perceived more negatively than when they make academic errors.…”
Section: Discussionmentioning
confidence: 65%
“…Forgetfulness in academic contexts seems to be viewed more normatively as children are rated as more likely to repeat these errors in the future. Finally, greater amounts of experience with children led to participants rating children more favourably in our trait composite overall suggesting that individuals with more knowledge of child development might be less critical of forgetfulness as they might be aware it is still developing during early and middle childhood (Furnham et al, 2003;Vale-Dias & Nobre-Lima, 2018).…”
Section: Age and Domain Effects On Repeatabilitymentioning
confidence: 94%
See 3 more Smart Citations